Inovasi Produk Sebagai Upaya Peningkatkan Volume Penjualan Krupuk Trasi “Dua Burung” - Novita Dwi Rachmawati; Husna Ni'matul Ulya (CV. Adiguna Kertosari, 2021)
The “Dua Burung” cracker business is located in Ketawang Village, Dolopo Madiun. This business has been established since 1987. Krupuk Trasi has become a specialty in Ketawang village because this type of cracker was first produced or produced in this village. Because it has been ogled by outsiders, finally a similar business with similar products appears. reduced coupled with the current situation, namely the outbreak of the corona virus causing the number of sales to decrease. Therefore, to increase sales, one of the efforts that are felt to increase the number of sales is to develop this traction cracker product. can increase sales because, the surrounding community who want to buy these crackers for their own daily consumption will prefer to eat products that can be eaten rather than raw products. People will be more interested because it will be more efficient than having to process raw crackers. So that this can attract buyers who will eventually increase sales volume in the Krupuk Trasi